2023
DOI: 10.3390/w15193325
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Wastewater Treatment Plant Effluent Water Quality Using Recurrent Neural Network (RNN) Models

Praewa Wongburi,
Jae K. Park

Abstract: Artificial Intelligence (AI) has recently emerged as a powerful tool with versatile applications spanning various domains. AI replicates human intelligence processes through machinery and computer systems, finding utility in expert systems, image and speech recognition, machine vision, and natural language processing (NLP). One notable area with limited exploration pertains to using deep learning models, specifically Recurrent Neural Networks (RNNs), for predicting water quality in wastewater treatment plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…For instance, Foschi et al [25] employed shallow artificial neural networks (ANNs) to predict the quality of sewage, and they reported that, although the shallow fully connected layer was unstable at mimicking the time dependency in the time series, the shallow ANN was superior at capturing the nonlinear correlations among the wastewater quality series. Based on time series analysis, Wongburi et al [26] employed long short-term memory networks (LSTMs) to predict forecast sewage quality to resolve nonlinear and long-term dependent intricacies within the wastewater quality. Yang et al [17] developed a principal component analysis-dynamic nonlinear autoregressive with exogenous inputs (PCA-NARX) model to forecast effluent quality.…”
Section: Deep Learning Methodsmentioning
confidence: 99%
“…For instance, Foschi et al [25] employed shallow artificial neural networks (ANNs) to predict the quality of sewage, and they reported that, although the shallow fully connected layer was unstable at mimicking the time dependency in the time series, the shallow ANN was superior at capturing the nonlinear correlations among the wastewater quality series. Based on time series analysis, Wongburi et al [26] employed long short-term memory networks (LSTMs) to predict forecast sewage quality to resolve nonlinear and long-term dependent intricacies within the wastewater quality. Yang et al [17] developed a principal component analysis-dynamic nonlinear autoregressive with exogenous inputs (PCA-NARX) model to forecast effluent quality.…”
Section: Deep Learning Methodsmentioning
confidence: 99%
“…Water quality parameter data exhibit nonlinearity and temporality. With the development of deep learning, Recurrent Neural Network (RNN) is more suitable for processing nonlinear time series compared to ANN [22]. Kumar et al [23] conducted a model prediction study on monthly river flow data using a RNN network and proved that RNN has high accuracy in predicting time series data.…”
Section: Introductionmentioning
confidence: 99%
“…Some deep learning networks are born to handle data with time steps, RNN (recurrent neural network) for instance, their hidden states can be passed along time steps, and RNNs (RNN and its variants) are successfully employed to various kinds of hydrology tasks [18][19][20][21][22][23][24][25]. In particular, to deal with short-term runoff prediction problems, a deep learning multi-dimensional ensemble method has proven to be effective [26,27].…”
Section: Introductionmentioning
confidence: 99%